TIPOLOGI ATAP BANGUNAN KELENTENG DI KOTA PONTIANAK - Elianty, Ferencia; Kalsum, Emilya; Zain, Zairin (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
Kelenteng is a place of worship for Confucianism, Buddhism, and Taoism, also known as the Tri Dharma Worship Place (TITD). The Kelenteng has its own characteristics that distinguish it from other places of worship. One of the most easily noticeable characteristics is on the roof of the Kelenteng. The roof of the Kelenteng generally uses the traditional Chinese roof shape. The shape of the temple building roof varies due to climate factors and the acculturation of its original regional architecture with local architecture. The diversity of roof shapes can also be seen from the principles of arranging the shapes found in the roof. This research was conducted using a qualitative approach with a descriptive method. Research data collection was carried out by field observation and literature study. Field observations were carried out by documentation and sketching. The sketch results will be digitized to obtain the shape of the temple roof. The final result of this research is to obtain the typology of the roof shape of the Kelenteng in Pontianak City. The Kelenteng roof in Pontianak City consists of two types, namely a combination of hip and gable roof (Hsuan Hsan) and a gable roof (Ngang Hsan). The dominant roof type used in Kelenteng in Pontianak City is the Hsuan Hsan roof type with a curved roof tip.